Studi Deskriptif Mengenai Psychological Well-Being pada Remaja SOS Desa Taruna Kinderdorf Bandung - Savitri, Jane; Kiswantomo, Heliany; -, Ratnawati (Zenit, 2012)
This research is to find out Psychological Well-Being (PWB) of  38  teenagers at SOS Desa Taruna Kinderdorf Bandung. The method uses descriptive method by using survey technique. Purposive sampling technique is used for selecting samples. The measuring tool used is the tool developed by Ryff (1989) and modified by the researcher. The tool consists of 84 items. The data is statistically analyzed in the form of perecentage using SPSS 17.0 and the result was 64 items with validity number between 0.308 to 0.657 and reliability of 0.82. Based on the data  analysis, the result shows that the  teenagers at SOS Desa Taruna Kinderdorf Bandung have equal percentage PWB degree, namely 50% of high PWB and 50% of low PWB. The PWB has six dimensions. They are influenced by some factors, among others related with age, sex, education level, and “Big Five Personality” types. The researcher suggests a further research on the contribution of some factors that  influence PWB towards the degree of PWB and its dimensions.  Furthermore, a further research is needed to be done for teenagers at Kinderdorf Bandung before and after living in the dormitory to know exactly if there is a different degree of PWB and its dimensions. The director of SOS Desa Taruna Kinderdorf Bandung is able to re-examine a caring system to teenagers who live outside Lembang and design a caring system that is more suitable for them in order to improve their PWB dimensions. Besides, psychologists at SOS Desa Taruna Kinderdorf Bandung are able to take a significant role in councelling, face to face or group councelling, improving low PWB and its dimensions of teenagers of SOS Desa Taruna Kinderdorf Bandung.  Keywords: psychological well-being, teenagers, SOS Desa Taruna Kinderdorf Bandung.